Cognitive Diagnostic Assessment Instrument with Individual Feedback for Language Receptive Learning on Multimodal Text - Anisah, Giati; Yuli Amreta, Midya (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Cognitive diagnostic assessment with individual feedback plays an important role in detecting students' cognitive strengths and weaknesses, providing directions for steps that teachers and students must take to follow up on this, as well as facilitating the clustering of students in preparing differentiated learning. This study aims to develop a cognitive diagnostic assessment instrument for receptive language learning on multimodal text with individualized feedback. This study is R&D research with an ADDIE design. The study involved grade 9 students with varying cognitive levels working through the questions, and the results were analyzed to develop individualized feedback for each student. Individualized feedback was then followed up by teachers and students in differentiated learning. We conducted interviews, questionnaires, and observations to gather data on the feasibility of the assessment instrument. Based on the results of the analysis, it can be concluded that a set of cognitive diagnostic assessment instruments along with individualized feedback produced in the study meets the requirements of validity, reliability, and readability, as well as applicability. In addition, this study shows that the cognitive diagnostic assessment with individualized feedback provides an overview of the receptive cognitive subcompetence of language in multimodal text that is mastered so that it facilitates the teacher in developing content, process, and target differentiated learning products for the next material. This research also contributes to addressing the long-standing criticism that language assessments fail to provide individualized feedback to link assessment to learning.